2015
DOI: 10.1681/asn.2015030321
|View full text |Cite
|
Sign up to set email alerts
|

Extrarenal Progenitor Cells Do Not Contribute to Renal Endothelial Repair

Abstract: Endothelial progenitor cells (EPCs) may be relevant contributors to endothelial cell (EC) repair in various organ systems. In this study, we investigated the potential role of EPCs in renal EC repair. We analyzed the major EPC subtypes in murine kidneys, blood, and spleens after induction of selective EC injury using the concanavalin A/anti-concanavalin A model and after ischemia/reperfusion (I/R) injury as well as the potential of extrarenal cells to substitute for injured local EC. Bone marrow transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 51 publications
5
31
1
Order By: Relevance
“…The kidney digestion protocol for flow cytometry has been described in detail elsewhere. 26 In brief, kidneys were cut into small pieces; digested in phosphate-buffered saline containing 1% fetal calf serum (ThermoFisher), collagenase type IA (0.25 mg/ml, Sigma-Aldrich), and DNase I (0.25 mg/ml, Sigma-Aldrich); and incubated for 40 minutes at 37°C. The cells were then filtered twice through 40-µm cell strainers (BD Biosciences), and erythrocytes were lysed using BD Pharm Lyse.…”
Section: Methodsmentioning
confidence: 99%
“…The kidney digestion protocol for flow cytometry has been described in detail elsewhere. 26 In brief, kidneys were cut into small pieces; digested in phosphate-buffered saline containing 1% fetal calf serum (ThermoFisher), collagenase type IA (0.25 mg/ml, Sigma-Aldrich), and DNase I (0.25 mg/ml, Sigma-Aldrich); and incubated for 40 minutes at 37°C. The cells were then filtered twice through 40-µm cell strainers (BD Biosciences), and erythrocytes were lysed using BD Pharm Lyse.…”
Section: Methodsmentioning
confidence: 99%
“…Second, antiangiogenic factors (e.g., thrombospondin 1 and endostatin) have been reported to be upregulated in several kidney diseases [61][62][63]. Third, the incompetence of endothelial progenitor cells potentially underlies insufficient capillary restoration [64], although recent studies have questioned the direct involvement of bone marrow-derived or circulating progenitor/stem cells in blood vessel regeneration [65,66].…”
Section: Sustained Capillary Rarefactionmentioning
confidence: 99%
“…In a mouse model of selective endothelial injury by Hohenstein et al [27, 28], BM-derived cells carrying markers of EPCs were found in injured kidneys and these cells were shown to contribute to subsequent healing of endothelial lesions. However, in another study, Sradnick et al investigated the potential role of EPCs in renal endothelial cell repair [29]. In this study, extrarenal cells were not found to replace any mature endothelial cells suggesting that endothelial repair depends on local mechanisms in acute endothelial injury model.…”
Section: Basic Concepts About Epcsmentioning
confidence: 75%